轉換與更新：中國大陸課堂教學話語研究Transformation and Renewal: Research on Classroom Teaching Discourse in Mainland China - 安桂清Gui-Qing An (Journal of Curriculum Studies, 2009)
隨著「語言學轉向」及話語分析的興起，課堂教學話語研究開始為人所矚目。中國大陸過去三十年的課堂教學話語研究呈現出兩種語絡：「非批判的方法」與「批判的方法」。其中前者又存在兩種取向：語義學取向與語用學取向。但嚴格意義的批判研究取向的教學話語分析至今仍處於起步階段。二十一世紀以來，在基礎教育課程改革的推動下，傳統課堂教學話語的運作方式有所轉變，教師與學生的身分、關係及觀念體系在覺醒的課堂教學話語實踐中部分得以重建。但課堂教學話語要真正成為一種「解放的」話語實踐，還有賴於教師「批判的語言意識」的發展。面對中國大陸課堂教學話語研究亟待突破的狀況，期待有更多的研究者以高度的使命感投身其中。 With the “linguistic turn” and the rise of discourse analysis, more attention has been paid to the research on classroom teaching discourse. There are two methods that are noncritical method and critical method in the research field of classroom teaching discourse in Mainland China over the past thirty years. Non-critical research includes two trends that are semantics trend and pragmatics trend. Speaking rigidly, critical research on classroom teaching discourse is still in its Starting period. Under the promotion of basic education curriculum reform, traditional operating modes of classroom teaching discourse have changed since 21 century. The identity, relation and idea system of teacher and student have been partly reconstructed because of the new classroom teaching discourse practice. However, classroom teaching discourse depends on the development of teachers’ critical language awareness if it truly becomes a kind of “emancipatory” discourse practice. Facing the condition that research on classroom teaching discourse need make an urgent breakthrough in Mainland China, we expect more researchers to devote themselves to the research on classroom teaching discourse with the high sense of mission.